Urea Cycle Disorders in Neonates: Six Case Reports - Kıymet Çelik; Demet Terek; Özgür Olukman; Mehtap Kağnıcı; Şükran Keskin Gözmen; Erkin Serdaroğlu; Şebnem Çalkavur; Sertaç Arslanoğlu (Galenos Yayinevi, 2017)
Urea cycle disorders are a group of diseases associated with hyperammonemia, which causes severe neurological sequelae, seizures and psychomotor retardation. In this study, six newborn cases diagnosed between 2010-2014 as citrullinemia Type I (four cases) and argininosuccinic aciduria (two cases) are presented in terms of clinical course and treatment responses.